Uncertainty evaluation in the differential measurements of power losses in a power drive system. (October 2021) - Caruso, M.; Di Tommaso, A.O.; Miceli, R.; Nevoloso, C.; Spataro, C.
Highlights: Analysis of standards related to PDS efficiency and power losses measurement. Uncertainty evaluation in absolute and differential power losses measurements. Accurate power losses variations measurements of PDS. Comparison of three measurement systems performances with different accuracy. Extended experimental analysis for measurement short-term repeatability assessment. Abstract: In order to guarantee a correct classification in the standardized energy efficiency classes, the current standards concerning the power drive systems prescribe that their power losses must be evaluated with great accuracy. This circumstance involves the usage of expensive measurement systems, since accurate instrumentation, skilled personnel and controlled environments are required. During the design stage of a power drive system, however, the measurement of the absolute value of its power losses is not always needed. Often, in fact, it is enough to assess the power losses variations caused by a modification of either hardware or software sections of the power drive system. In these cases, it is possible to evaluate the losses by means of differential measurements. The aim of the paper is the uncertainty characterization of this kind of measurements. The analysis is carried out by experimentally comparing the performances of three measurement systems, each one characterized by different accuracy and cost. The results show that even the systems not adequate to measure the absolute values of power losses can be used to accurately assess their variations.